2011
DOI: 10.1371/journal.pone.0019826
|View full text |Cite
|
Sign up to set email alerts
|

Expression of HLA Class II Molecules in Humanized NOD.Rag1KO.IL2RgcKO Mice Is Critical for Development and Function of Human T and B Cells

Abstract: BackgroundHumanized mice able to reconstitute a surrogate human immune system (HIS) can be used for studies on human immunology and may provide a predictive preclinical model for human vaccines prior to clinical trials. However, current humanized mouse models show sub-optimal human T cell reconstitution and limited ability to support immunoglobulin class switching by human B cells. This limitation has been attributed to the lack of expression of Human Leukocyte Antigens (HLA) molecules in mouse lymphoid organs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
219
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(231 citation statements)
references
References 50 publications
12
219
0
Order By: Relevance
“…These include transient approaches such as hydrodynamic injection of plasmid DNA (34), injections of cytokines, and infections of mice or CD34 + cells with lentiviruses (35)(36)(37). Alternatively, transgenic expression of human MHC molecules has been demonstrated to improve the development of antigen-specific immune responses in vivo (38)(39)(40). Nonetheless, overexpression of cytokines might also have detrimental side effects due to the unphysiological expression such as in mice transgenic for SCF, GM-CSF, and IL-3 (41).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include transient approaches such as hydrodynamic injection of plasmid DNA (34), injections of cytokines, and infections of mice or CD34 + cells with lentiviruses (35)(36)(37). Alternatively, transgenic expression of human MHC molecules has been demonstrated to improve the development of antigen-specific immune responses in vivo (38)(39)(40). Nonetheless, overexpression of cytokines might also have detrimental side effects due to the unphysiological expression such as in mice transgenic for SCF, GM-CSF, and IL-3 (41).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the increased functionality in SIRP-DKO mice is likely the result of improved selection and differentiation of T cells in vivo due to overall higher numbers of human immune cells. Similarly, HLA-DR4 transgenic mice and humanized mice that are generated by cotransplantation of CD34 + cells and human fetal thymus pieces have improved HLA-restricted T cell responses and also improved antigen-specific antibody responses (40,46). However, further studies will be needed to characterize and quantify antigenspecific T cell responses in hSIRPa-DKO mice.…”
Section: Discussionmentioning
confidence: 99%
“…Antigen-specific IgG was produced in HLA class II transgenic NSG mice. 43 Real humanized mice are expected to be generated in the near future by improving immunodeficient mice.…”
Section: Current Advances In Humanized Mouse Models R Ito Et Al 209mentioning
confidence: 99%
“…25 In addition, recent reports have shown that new mouse strains that express HLA-DR mounted an antigen-specific IgG response upon immunization. 43 Collectively, B cells in humanized mice maintain the ability to mediate humoral immune reactions.…”
Section: Lymphoid Cellsmentioning
confidence: 99%
“…Factors that may impact in the inefficient lymphatic development in HIS mice include the absence of human histocompatibility molecules and a poor humanized cytokine environment. To overcome this deficiency, approaches including delivery of recombinant cytokines (32,33), transplantation of fetal lymphatic tissue along with HPCs (34,35) or the use of transgenic strains constitutively expressing the MHC class I (36) and II (37) or critical hematopoietic cytokines (38) have been described recently. Despite some improvement, these single strategies allowed a limited improvement in B and T cell responses against human viral challenges.…”
Section: Cd83mentioning
confidence: 99%